The Effect Of Management Ownership, Leverage, Firm Size, And Profitability On Social Disclosure In Annual Reports Of Manufacturing Company (Empirical Study On Manufacturing Company Listed In Idx) (Proceeding Fakultas Ekonomi, 2012)
Products  of accounting  in  the form of financial statement–annual  report is the exposure of the report containing the accountability         of    the   management               of operational  activities  to  the  shareholders, but now need to extend this paradigm to be accountable to all  stakeholders. This study is        an        empirical       study   conducted       in manufacturing companies listed in IDX are intended to identify and examine the effect of  management  ownership,  leverage,  size, and                   profitability      on        social   disclosure (Sustainable   Reporting)  in  their  annual reports during the  period 2007-2010. The results of                     this       study        indicate       that management  ownership  and  leverage  has no   effect  on        the         disclosure       of     social reporting in annual reports, whereas firm size and profitability have an influence on social disclosure in annual reports. Keywords: Social  Disclosure,  Sustainable Reporting,  Management  Ownership, Leverage, Firm Size, Profitability